HRCT evaluation of microtia: A retrospective study - Aruna R Patil; Ashu Bhalla; Pankaj Gupta; Deepali Goyal; Sreenivas Vishnubhatla; Anurag Ramavat; Suresh Sharma (Indian Journal of Radiology and Imaging, 2012)
Purpose: To determine external, middle, and inner ear abnormalities on high-resolution computed tomography (HRCT) of temporal bone in patients with microtia and to predict anatomic external and middle ear anomalies as well as the degree of functional hearing impairment based on clinical grades of microtia. Materials and Methods: It was a retrospective study conducted on Indian population. Fifty-two patients with microtia were evaluated for external, middle, and inner ear anomalies on HRCT of temporal bone. Clinical grading of microtia was done based on criteria proposed by Weerda et al. in 37 patients and degree of hearing loss was assessed using pure tone audiometry or brainstem-evoked response in 32 patients. Independent statistical correlations of clinical grades of micotia with both external and middle ear anomalies detected on HRCT and the degree of hearing loss were finally obtained. Results: The external, middle, and inner ear anomalies were present in 93.1%, 74.5%, and 2.7% patients, respectively. Combined cartilaginous and bony external auditory canal atresia (EAC) was the most common anatomic abnormality in our group of microtia patients. Hypoplastic mesotympanum represented the commonest middle ear anomaly. The incidence of combined ossicular dysplasia and facial canal anomalies was lower as compared to other population groups; however, we recorded a greater incidence of cholesteatoma. Both these factors can have a substantial impact on outcome of patients planned for surgery. We found no significant association between grades of microtia and external or middle ear anomalies. Similarly, no significant association was found between lower grades of microtia (grade I and II) and degree of hearing loss. However, association between grade III microtia and degree of hearing loss was significant. A significant association between congenital cholesteatoma and degree of pneumatization of atretic plate and mastoid process not previously studied was also recorded in our study.